Quantifying nitrogen uptake and translocation for mature trees: an in situ whole-tree paired 15N labeling method. (20th May 2021) - Zhu, Feifei; Dai, Luming; Hobbie, Erik A; Qu, Yuying; Huang, Dan; Gurmesa, Geshere A; Zhou, Xulun; Wang, Ang; Li, Yinghua; Fang, Yunting
Abstract: Nitrogen (N) is one of the major nutrients limiting plant growth in terrestrial ecosystems. To avoid plant–microbe competition, previous studies on plant N uptake preference often used hydroponic experiments on fine roots of seedlings and demonstrated ammonium preference for conifer species; however, we lack information about N uptake and translocation in the field. In this paper, we described a method of in situ paired 15 N labeling and reported the rates and time course of N uptake and translocation by mature trees in situ. We added 15 N-enriched ammonium or nitrate, together with the nitrification inhibitor dicyandiamide, to paired Larix kaempferi (Lamb.) Carr (larch) trees from 30-, 40- and 50-year-old plantations. Fine roots, coarse roots, leaves and small branches were collected 2, 4, 7, 14 and 30 days after labeling. Nitrate uptake and translocation averaged 1.59 ± 0.16 μg 15 N g −1 day −1, which is slightly higher than ammonium (1.08 ± 0.10 μg 15 N g −1 day −1 ), in all tree organs. Nitrate contributed 50–78% to N uptake and translocation, indicating efficient nitrate use by larch in situ. We observed no age effect. We suggest that sampling leaves after 4 days of 15 N labeling is sufficient to detect mature tree N uptake preference in situ. Whole-tree 15 N-ammonium recovery equaled that of 15 N-nitrate 30 days after 15 N addition, implying the importance of both ammonium and nitrate to mature larch N use in the long run. We conclude that our method is promising for studying mature tree N uptake preference in situ and can be applied to other conifer and broadleaf species. We suggest using highly enriched 15 N tracer to overcome soil dilution and a nitrification inhibitor to minimize ammonium transformation to nitrate. Our study revealed mature tree N preference in situ and demonstrated the strong contribution of nitrate toward mature larch growth on soils rich in nitrate.